Tingkat Ekspresi Emosi pada Caregiver Skizofrenia di Kecamatan Kersamanah, Kabupaten Garut - Sarah Khairunnisa Zahrani; Farida Coralia (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. Kersamanah District is the sub-district with the highest number of people that have schizophrenia in Garut with a total of 107 sufferers, and the Sukamerang Public Health Center is the only health facility located there, along these lines, Kersamanah District is called the